Health Care Spending on Diabetes in the U.S., 1996–2013 - Squires, Ellen (Diabetes Care, 2018)
OBJECTIVE: Health care spending on diabetes in the U.S. has increased dramatically over the past several decades. This research describes health care spending on diabetes to quantify how that spending has changed from 1996 to 2013 and to determine what drivers are increasing spending. RESEARCH DESIGN AND METHODS: Spending estimates were extracted from the Institute for Health Metrics and Evaluation’s Disease Expenditure 2013 database. Estimates were produced for each year from 1996 to 2013 for each of 38 age and sex groups and six types of care. Data on disease burden were extracted from the Global Burden of Disease 2016 study. We analyzed the drivers of spending by measuring the impact of population growth and aging and changes in diabetes prevalence, service utilization, and spending per encounter. RESULTS: Spending on diabetes in the U.S. increased from $37 billion (95% uncertainty interval $32–$42 billion) in 1996 to $101 billion ($97–$107 billion) in 2013. The greatest amount of health care spending on diabetes in 2013 occurred in prescribed retail pharmaceuticals (57.6% [53.8–62.1%] of spending growth) followed by ambulatory care (23.5% [21.7–25.7%]). Between 1996 and 2013, pharmaceutical spending increased by 327.0% (222.9–456.6%). This increase can be attributed to changes in demography, increased disease prevalence, increased service utilization, and, especially, increases in spending per encounter, which increased pharmaceutical spending by 144.0% (87.3–197.3%) between 1996 and 2013. CONCLUSIONS: Health care spending on diabetes in the U.S. has increased, and spending per encounter has been the biggest driver. This information can help policy makers who are attempting to control future spending on diabetes.